ALGORITHMIC DEPENDENCY AND THE PROCESS OF DIGITAL ZOMBIFICATION: THREATS TO SOCIAL STABILITY AND GLOBAL SECURITY MECHANISMS (Modern American Journal of Social Sciences and Humanities, 2026)
This article provides a scientific analysis of the impact of modern media platform algorithms (TikTok, Instagram Reels, YouTube Shorts) on human neurobiology and behavior in the context of global digital transformation. The study highlights the specific characteristics of algorithmic dependency, dopamine stimulation, and the resulting processes of "digital manqurtization" emerging in the digital space. Furthermore, the cognitive threats posed to social stability by phenomena such as information manipulation, filter bubbles, disinformation, and trolling are investigated. Finally, systemic recommendations and global and national information security mechanisms aimed at neutralizing these threats and enhancing media literacy are proposed.